(untitled) (International Journal of Current Engineering and Technology, 2015)
The Big Data is the buzzword in present days across the globe. As there is a huge data generated by different sources such as business people, marketing, education, engineering, medicine, social media, on-line transactions, call centers, sensors, web logs and telecommunication. There is a need to manage the risk associated with the collection, storage, retrieval and analysis of such enormous data. Big data analytics is emerged as a core business practice that firms use to understand their business. Business intelligence and analytics are in high demand as organizations seek to use information assets to improve business outcomes. To meet the demand of the Business intelligence (BI) vendors are looking at predictive analytics to understand customer behavior in new ways. E –Business merchants are collecting and analyzing data to discover shopping patterns that will predict value and understand consumer experiences in digital context. In this paper we described the evolution of different analytics and the impact of big data on business intelligence and also the future scope of predictive analytic with the existing business which will yield a better and cost reduced outcomes.